2000
DOI: 10.1073/pnas.140122097
|View full text |Cite
|
Sign up to set email alerts
|

Activation of polyamine catabolism in transgenic rats induces acute pancreatitis

Abstract: Polyamines are required for optimal growth and function of cells. Regulation of their cellular homeostasis is therefore tightly controlled. The key regulatory enzyme for polyamine catabolism is the spermidine͞spermine N 1 -acetyltransferase (SSAT). Depletion of cellular polyamines has been associated with inhibition of growth and programmed cell death. To investigate the physiological function SSAT, we generated a transgenic rat line overexpressing the SSAT gene under the control of the inducible mouse metallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 36 publications
(40 reference statements)
3
80
0
1
Order By: Relevance
“…The effects of overexpression of SAT1 were previously reported by others using cell lines overexpressing SAT1 stably or in an inducible manner (22)(23)(24)33), SAT1 transgenic mice (34)(35)(36), and a SAT1 adenovirus (37,38). Although retardation of growth and decreases in spermidine and spermine were consistently associated with SAT1 overexpression, the degree of growth inhibition and polyamine depletion were much lower than those reported in this study.…”
Section: Discussionmentioning
confidence: 56%
“…The effects of overexpression of SAT1 were previously reported by others using cell lines overexpressing SAT1 stably or in an inducible manner (22)(23)(24)33), SAT1 transgenic mice (34)(35)(36), and a SAT1 adenovirus (37,38). Although retardation of growth and decreases in spermidine and spermine were consistently associated with SAT1 overexpression, the degree of growth inhibition and polyamine depletion were much lower than those reported in this study.…”
Section: Discussionmentioning
confidence: 56%
“…1A displays the typical polyamine pattern in the liver of SSAT overexpressing rats. Putrescine pool was greatly increased, whereas the spermine level was decreased when compared with wild-type rat liver where putrescine remains almost undetectable (8). An exposure of the rats to the polyamine oxidase inhibitor MDL72527 expectedly greatly reduced putrescine content and expanded the pool of N 1 -acetylspermidine (Fig.…”
Section: Purity Of ␣-Methylated Polyamine Analogs: Nmr and Highmentioning
confidence: 92%
“…Transgenic Rats and the Studies of ␣-Methylated Spermine Analogs-The production of transgenic rats has been described in detail earlier (8). Partial hepatectomy of the transgenic rats was carried out essentially as described in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…A transgenic rat model has been used to demonstrate that a depletion of pancreatic spermidine and spermine, through overexpression of the catabolic polyamine enzyme spermidine/spermine N 1 -acetyltransferase (SSAT), leads to onset of acute pancreatitis (Alhonen et al, 2000), and this could be prevented with the application of 1-methylspermidine, a metabolically stable analogue of spermidine (Räsänen et al, 2002). It should be kept in mind that Nishimura et al (2009) demonstrated a steady-state of polyamines were present in the pancreas even with ageing, but given that the total body pool of polyamines generally decreases with age, diet-derived polyamines could still be an important source to maintain pancreatic polyamine concentrations.…”
Section: Other Potential Health Benefits Of Polyaminesmentioning
confidence: 99%